Validation Method of the Cellulose Triacetate-Based Optode Membrane for Fe(III) Detection in Water Samples - Zulhan Arif; Sri Sugiarti; Eti Rohaeti; Irmanida Batubara (Jurnal Kimia Sains dan Aplikasi, 2025)
Iron contamination in water is a threat to human health and the environment. This contamination requires a fast and efficient detection method. Method validation is integral to method development, ensuring alignment with the intended objectives. This research aims to validate a method for selective detection of Fe(III) based on cellulose triacetate (CTA) optode membrane. The optode membrane was prepared by mixing CTA, plasticizers, Aliquat-336, and thiocyanate as selective reagents. The validation of the optode membrane was evaluated based on validation performance parameters. The Fe(III) optode membrane detection demonstrated a linear response with a determination coefficient of 0.9972 within a concentration range of 0.1–4.0 mg/L, the detection limit of 0.0553 mg/L, quantitation limit of 0.1676 mg/L, precision 3.01%, intermediate precision of 3.03% and 3.01%, the accuracy of 101.62%. The optode membrane exhibited good selectivity with a value of -0.4580 and -0.2748 against Pb(II) and Cr(VI), respectively, sensitivity of 1.05 × 107 M-1 cm-1 and color formation stability %RSD of 3.14%. The application of real samples shows no significant difference between the UV-Vis spectrophotometry and optode membrane methods at a 95% confidence level (α = 0.05). The validation results offer a valuable perspective into whether this method can be adopted as a new approach or as an alternative to existing methods for cation analysis in water samples.